Economic and Fiscal Impacts of Venezuelan Refugees and Migrants in Brazil - Shamsuddin, Mrittika; Acosta, Pablo Ariel; Battaglin Schwengber, Rovane; Fix, Jedediah; Pirani, Nikolas (World Bank, Washington, DC, 2021)
As more and more Venezuelans leave their country, fleeing the economic and social crisis, the number of Venezuelans in Brazil has risen steadily since 2016, constituting about 18 percent of Brazil's 1.3 million refugee and migrant population as of October 2020. Although the economic gains of immigration are well-documented in the literature, the impacts of forced displacement on the labor market and government budget are mixed and have mainly focused on developed countries. This paper extends the previous literature by exploring the short-run fiscal impact of Venezuelan refugees and migrants on the public expenditure and revenue of Roraima, the state bordering the República Bolivariana de Venezuela at the north and the main gateway of the Venezuelan refugees and migrants entering Brazil, and by investigating their impact on its labor market. Using various administrative and survey data and a regression discontinuity framework, the paper finds that the population shock caused by the influx of forcibly displaced Venezuelans in the short-run did not have any statistically significant effect on the fiscal variables of Roraima. On the labor market, the paper finds that the population shock translated into an increase in unemployment among women and a decrease in employment among women and low skilled workers in the short-run. The effects on earnings are heterogenous across industries, but mainly positive for the high skilled and male workers, suggesting a need for cross-cutting policies that target the most vulnerable host population as well as the forcibly displaced.